Evaluation of diastolic dysfunction in multi-transfused thalassemia patients - Vithalani, Mitsu P.; Vyas, Bhadresh R.; Makvana, Namrata (International Journal of Contemporary Pediatrics, 2023)
Background: An important complication of thalassemia is iron deposition in the cardiac tissue resulting in degeneration, fibrosis and dysfunction. Cardiac disease is the primary cause of death. Aims and objectives were to detect early cardiac involvement in patients with transfusion dependent thalassemia by conventional doppler echocardiography and tissue doppler imaging while they are still asymptomatic. Methods: 150 patients in the age group of 2-18 years who were receiving regular and frequent blood transfusions were enrolled in this study. Institutional ethical clearance was taken. After informed consent, 2D echocardiography was performed on all the patients. Previous blood reports reviewed. Various parameters like mitral flow pattern, LVEF and Tricuspid regurgitant jets were taken into account to diagnose cardiac dysfunction. Results analysed by standard statistical tests. Results: Out of 150 patients, 58% were males and 42% were female patients. The 13 (8.6%) patients were diagnosed as having diastolic dysfunction. Out of 150, majority (86.6%) were below the age of 15 years, 81.33% children were diagnosed as having thalassemia before the age of 2 years, 97% patients were on regular iron chelation therapy, 32% patients had pre-transfusion Hb <7 gm/dl, 78.66% patients had S. ferritin levels >2500 ng/ml and more number of males (7.33%) have undergone splenectomy than females. Conclusions: Diastolic dysfunction on Doppler echocardiography is an early sign of myocardial dysfunction in patients with beta thalassemia.